2015
DOI: 10.1590/0102-311x00056414
|View full text |Cite
|
Sign up to set email alerts
|

Domínios de atividade física em comunidades quilombolas do sudoeste da Bahia, Brasil: estudo de base populacional

Abstract: This study aimed to describe the prevalence of physical activity (PA) and associated factors in various domains (leisure-time, work, home, and commuting)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 29 publications
2
11
1
12
Order By: Relevance
“…15 The disparities in prevalence rates can be explained, among other factors, by the daily lives of the different population groups. People who live in rural areas tend to have more active jobs and more active movement between one place and another, 15,18 which have impact on increased burning of energy, compared to those who live in urban spaces. However, it must be remembered that use of different instruments for measuring and assessing PA can also generate discrepant results with regard to the outcome investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 The disparities in prevalence rates can be explained, among other factors, by the daily lives of the different population groups. People who live in rural areas tend to have more active jobs and more active movement between one place and another, 15,18 which have impact on increased burning of energy, compared to those who live in urban spaces. However, it must be remembered that use of different instruments for measuring and assessing PA can also generate discrepant results with regard to the outcome investigated.…”
Section: Discussionmentioning
confidence: 99%
“…17 A study with quilombolas (maroons) in a municipality in the southeast of Bahia state indicated that they are more active when at work than in their free (or leisure) time, scoring 42.1% and 13.1%, respectively. 18 Mussi et al 19 also identified a low amount of PA in the free time of a Bahian quilombola community living on the banks of the São Francisco river.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Este estudo revelou que as condições socioeconômicas das famílias quilombolas investigadas eram precárias, marcadas pela baixa escolaridade dos adultos, baixa renda familiar, alta dependência de programas de redistribuição de renda (Bolsa Família) e núcleos familiares com até 5 pessoas (embora esta constituição seja menor do que no passado para os grupos populacionais tradicionais da Amazônia) 31 . Diversas pesquisas no nordeste e norte do país tem também demonstrado que nas comunidades quilombolas predominam a baixa escolaridade e baixa renda familiar 32,33,34 .…”
Section: Discussionunclassified
“…Com relação ao saneamento ambiental, as condições de infraestrutura dos remanescentes de quilombos investigados foram consideradas precárias, pois a maioria das casas não possuía sistema de esgoto e nem fontes de água e tratamento adequado dos dejetos, situação similar à observada em outra pesquisa realizada com quilombolas das diversas regiões do Pará 34 . Esta é também a realidade de outros estados, como entre os remanescentes de quilombos do Vale do Mucuri, Minas Gerais 37 Ao considerar os aspectos comportamentais, um estudo de base populacional, realizado com quilombolas do sudoeste da Bahia, mostrou que 54,1% deles nunca havia fumado 32 , corroborando parcialmente com os resultados deste estudo. Vale ressaltar que, em populações que residem distante das zonas urbanas, é mais comum o uso de cigarros feitos pelos próprios fumantes do que a utilização de cigarros e outros produtos industrializados 38 .…”
Section: Discussionunclassified